P 106 Functional magnetic resonance imaging of appetitive aggression in martial artists. Issue 10 (October 2017) - Schöne, M.; Breitschuh, S.; Tozzi, L.; Kaufmann, J.; Strumpf, H.; Fenker, D.; Frodl, T.; Bogerts, B.; Schiltz, K.
Abstract : Background: The direct execution as well as the visual perception of violence can have a hedonistic aspect and elicit positive arousal. (Elbert et al., 2010 ) So far, neurobiological correlates of this "appetitive" form of aggression have not been investigated in healthy subjects. Using functional magnetic resonance imaging (fMRI), we tested if subjects who act violently (martial artists) showed greater brain responses to violent images compared to controls in the subcortical reward-associated areas of the mesolimbic dopaminergic system. (Urban et al., 2012 ). Methods: Sixteen male martial artists and 26 male controls took part in the study. As a measure of aggressiveness, we used the FAF questionnaire ("Fragebogen zur Erfassung von Aggressivitätsfaktoren"). During our event-related fMRI paradigm, 54 violent and 54 neutral pictures were shown in a randomized order. After their presentation, a square or circle was briefly projected on the pictures and the subjects then decided which shape had been shown by pressing a button. Independent of their response, a reward randomly followed their answer in 50% of trials. A first-level general linear model (GLM) analysis was run, obtaining the contrast values for violent > neutral pictures. Average contrast values were then extracted from the bilateral nucleus accumbens, amygdala and orbitofrontal cortex (OFC). These values were entered in a GLM to investigate main effects and interactions of the group factor and FAF scores, using age as a covariate. Results: Across all participants, higher aggressiveness scores were associated with less activation of the bilateral OFC while watching violent pictures in contrast to neutral ones (left OFC: F df=1 = 4.201, p = .048; right OFC: F df=1 = 4.097, p = .050). On average, martial artists had a higher activation in the left amygdala while watching violent pictures in contrast to controls ( F df=1 = 13.333, p = .001). Furthermore, the more aggressive martial artists were, the smaller their activation in the left amygdala in this condition ( F df=1 = 7.998, p = .008). Discussion: Activations in the OFC have been linked to emotional regulation. (Philipps et al., 2008 ) While watching violent pictures, more aggressive people might show a reduced frontal inhibition of subcortical areas involved in emotion generation. The amygdala is activated by presentation of affective and motivationally triggering stimuli (Rosell and Siever, 2015 ), e.g. watching a fight between two people. There might be different mechanisms in both groups to deal with aggression.